IOT-BASED REMOTE LIGHT CONTROL SYSTEM USING BOT TELEGRAM APPLICATION (CASE STUDY OF SMP AL WASHLIYAH CIREBON) - Syaiful Haq Al Furuqi; Muhamad Abu Hafsin; Haryono Haryono (Informatika, Universitas Jenderal Soedirman, 2022)
Advances in technology nowadays could make it easier for human beings in order to save time doing work that is commonly done. Smartphones are currently developing rapidly, and at the moment social media applications can be used to emerge as remote controllers which could manage electronic devices remotely. This study objectives to construct an IoT-based remote light control system using the telegram application. The consequences of this have a look at are predicted to save the user's time to turn on or turn off the lights remotely. Users only need to open the telegram application, then select the bot constructed to control the lights, and be asked to press the available commands. The consequences of this study take a look at the telegram bot application can turn the lights on and off properly, this has a delay less than 60 seconds according to the connection used, for every command that is pressed from the telegram bot utility.